Quality of Academic Service during the COVID-19 Pandemic at the Universitas Muhammadiyah Sinjai - Muhammad Takdir; Baharuddin Baharuddin; Sitti Hardiyanti Arhas; Irman Irman (Jurnal Ad'ministrare, 2021)
The government, through the ministry of education and culture, urges universities to monitor and assist students in learning from home. the type of research chosen is qualitative research. The data collection techniques used in this study were interviews, observation, and documentation. Meanwhile, the data analysis techniques used were data reduction, data presentation, and verification. Academic services during the COVID-19 pandemic at the Universitas Muhammadiyah Sinjai ran effectively according to the rules that had been set and were running according to the expected goals, this was seen from the service for student proposal examinations, the lecture process, and new student admissions